Dynamic Thrust Redistribution System for Coaxial Hexacopter H-Frame Under Motor Failure Contingencies N-1 - Subramaniam, Shankar; Mohd Ariff, Mohd Aifaa (Evolution in Electrical and Electronic Engineering, 2023)
Unmanned aerial vehicles (UAVs) have crucial applications across industries, emphasizing the importance of maintaining stability and preventing crashes, particularly in the event of motor failure. The research highlights motor failure as a significant cause of UAV crashes and its potential consequences, such as damage to batteries and agricultural productivity. The research involve creating a simulation model of a coaxial hexacopter's propulsion system, designing a control system for stability during motor failure, and analyzing the system's performance in terms of pitch, roll, and yaw axis and speed of motor. The project's scope focuses on a specific motor failure scenario in a coaxial hexacopter with an H-frame configuration, utilizing Simcenter Amesim software for comprehensive modeling and analysis. The findings demonstrate that the hexacopter successfully stabilized after applying the contingency counter, which involved increasing motor speed to generate more thrust and stabilize the frame. The hexacopter briefly descended by 0.2 meters, then slowly returned to the desired altitude. This showed that the hexacopter could keep its altitude stable even with a defective motor. The coaxial configuration and selective motor activation facilitated easy stabilization by redistributing thrust. The future works of this research include validating the simulation model with real-world data, enhancing the hexacopter response and stability with advanced control algorithms, and refining the simulation model with advanced techniques and data.